2018
DOI: 10.5713/ajas.17.0921
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation with fermented and non-fermented brown algae by-products on laying performance, egg quality, and blood profile in laying hens

Abstract: ObjectiveThis study was conducted to investigate the effects of dietary supplementation with fermented and non-fermented brown algae by-products on the laying performance, egg quality, relative organ weight, and blood profile of laying hens.MethodsHy-Line Brown chickens (n = 180; 70-week-old) were randomly divided into 5 groups with 4 replicates per group (3 hens per cage, 4 cages per replicate), and fed with 5 experimental diets, namely the basal control diet (CON) or the control diet supplemented with 0.5% b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 19 publications
7
37
1
Order By: Relevance
“…These results are in agreement with the observations of Rizk et al (2017) who reported that supplementing layer diets with green and brown seaweeds improved laying performance and egg production. In the present study, the addition of two types of GS and BS in the feed did not affect FC in layer Japanese quails, and similar results were observed in other studies (Carrillo et al, 2008;Choi et al, 2018). However, FCR was significantly affected due to dietary GS and BS supplementations, these results may be due to that green and brown seaweeds have been improved animal immune status by decreasing microbial load in the digestive tract, which reflect on feed metabolism and improved feed conversion ratio (Wang et al, 2013a, b).…”
Section: Results and Discussion Laying Performance And Egg Productionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are in agreement with the observations of Rizk et al (2017) who reported that supplementing layer diets with green and brown seaweeds improved laying performance and egg production. In the present study, the addition of two types of GS and BS in the feed did not affect FC in layer Japanese quails, and similar results were observed in other studies (Carrillo et al, 2008;Choi et al, 2018). However, FCR was significantly affected due to dietary GS and BS supplementations, these results may be due to that green and brown seaweeds have been improved animal immune status by decreasing microbial load in the digestive tract, which reflect on feed metabolism and improved feed conversion ratio (Wang et al, 2013a, b).…”
Section: Results and Discussion Laying Performance And Egg Productionsupporting
confidence: 92%
“…Formation of eggshell was reported to be affected by minerals, such as Ca, P, Mg, K (NRC, 1994). In current study, dietary supplementation with GS and BS included many minerals necessary for eggshell formation (Makkar et al 2016;Choi et al 2018). However, in this study, there was no difference in the quality of eggs due to all the minerals needed to form eggshell were provided in all experimental feeds.…”
Section: Results and Discussion Laying Performance And Egg Productionmentioning
confidence: 76%
See 1 more Smart Citation
“…Elevation in plasma GOT activity indicates hepatic injury. More GOT and GPT are released into the bloodstream when the liver or heart cells are impaired (Saleh 2014;Choi et al 2018). It has been reported that the alteration of GPT might be attributed to the synthesized fat level (Dongare et al 2013;Saleh 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that triglyceride in the plasma of the antibiotic group and experiment group I was increased, but decreased in the experimental group II (P > 0.05). In the study of Choi et al (2018 supplementation of fermented brown seaweed in the feed could signi cantly increase triglyceride and cholesterol in the blood of laying hens (P < 0.05) [49]. But Zhao et al (2013) reported that fed with fermented Ginkgo-leaves has an increased effect on triglyceride and cholesterol in blood plasma [50].…”
Section: The Effect Of Bacillus Velezensis On Biochemical Indices In mentioning
confidence: 98%